Reflections about the Use of Information and Communication Technologies in Accounting Education. (20th February 2015) - Gaviria, Diana; Arango, Juan; Valencia, Alejandro
Abstract: The teaching of accounting sciences requires innovative alternative methodologies that allow a greater dynamism in students' learning processes, encouraging their autonomy in order to foster greater understanding and ownership of accounting topics covered in class. In that sense, the use of ICT for educational purposes has been positioned as a dynamic and interactive alternative that allows the application of knowledge and encourages the feedback in the learning process. This paper aims to reflect on the use of ICT in accounting education as a strategy to improve teaching and learning processes in students of the Department of Finance of Metropolitan Institute of Technology of Medellin. It is proposed a teaching method with a learning virtual object through a virtual mediator of accounting formulations. It has a pedagogical purpose of providing students with a conceptual and practical tool to interpret and analyze accounting and financial topics at the enterprise level. It is observed that the interaction between accounting graph logic and logic of dynamic perception facilitates the processes of teaching and learning in the disciplines of accounting and finance. It is reflected in greater motivation and understanding of mathematical equations in financial area that will carry out to experimentation of knowledge learned in the classroom.